Green Accounting as Part of PT Halindo Berjaya Mandiri's Corporate Social Responsibility In Mitigating Environmental Risks - Harahap, Nurmala Sari; Yenni Samri Juliati Nasution; Hendra Hermain (Amkop Management Accounting Review (AMAR), 2025)
This study aims to examine in depth how the implementation of green accounting is carried out as a form of corporate social responsibility in order to reduce environmental risks at PT Halindo Berjaya Mandiri, a company engaged in the fisheries sector and previously experienced a decline in reputation due to allegations of environmental pollution. This study uses a qualitative approach with an in-depth interview method conducted with management, accounting staff, and officers who handle the company's waste management. The findings of this study indicate that the company has begun implementing the concept of green accounting, especially in the form of recording costs related to waste management and the construction of wastewater treatment plants (IPAL). However, the implementation is still limited to simple recording and has not been supported by a structured and separate recording system in detail. Nevertheless, this initial step is considered to have had a positive impact, especially in reducing the potential for environmental pollution and increasing the company's internal awareness of the importance of maintaining environmental sustainability.